Effects of feeding combinations of soybean and linseed oils on productive performance and milk fatty acid profile in grazing dairy cows - Antonacci, Liliana; Gagliostro, Gerardo Antonio; Cano, Adriana Virginia; Bernal, Claudio Adrián (2017)
Thirty-six grazing dairy cows were used to determine the effect of combinations of soybean (SO), and linseed (LO) oils on milk production, composition and milk fatty acid (FA) profile. Treatments were a basal control diet (56% pasture, 44% concentrate) or the control diet supplemented with oils at 4% of estimated total dry matter (DM) intake. Oils were manually mixed to the concentrate in pure forms (SO100 or LO100) or in blends (%w/w) at SO75 - LO25, SO50 - LO50 and SO25 - LO75. Concentrate and oils were thoroughly consumed. Pasture intake (kg DM/cow·day) was 9.27 in control and decreased (p < 0.05) in SO25 - LO75 (8.09) and LO100 (8.98). Total DM intake (kg/cow·day) in control (16.47) increased (p < 0.05) to 17.04 in SO100 and 17.20 in SO75. Yield of fat corrected milk (4% FCM) averaged 20.73 kg in control resulting higher in SO75 (23.73 kg). Milk fat content (g/100g) in control averaged 3.40 and decreased to 2.79 in SO50-LO50 and to 3.06 in SO25 - LO75 treatments. Milk protein content was not affected and milk protein yield increased in SO100 (11%) and SO75 - LO25 (21%) over Control (0.729 kg/cow·day). Milk basal (Control) content (g/100g FA) of C12:0 (2.58), C14:0 (10.21) and C16:0 (25.69) was reduced (p < 0.05) to 1.64, 6.82 and 19.70 respectively in oil supplemented cows. Basal content of C12:0 to C16:0 averaged 38.48 g/100g FA and decreased (27.4%) after oil intake. Basal trans-10 C18:1 (0.46 g/100g FA) increased (p < 0.01) in SO100 (1.48) and SO50-LO50 (1.80). Basal level (g/100g FA) of vaccenic acid (trans-11 C18:1, VA) averaged 3.49 and increased (135%) after oil intake with maximum values observed in LO100 (8.17) and SO50 - LO50 (9.20). Rumenic acid (cis-9, trans-11 C18:2, RA) level (g/100g FA) in milk from Control cows (1.56) increased (p < 0.05) to 3.03 (SO100), 3.21 (SO75 - LO25), 3.24 (SO50 - LO50), 2.33 (SO25 - LO75) and 2.96 (LO100). Results obtained confirmed a great milk fat plasticity in response to PUFA feeding in grazing dairy cows which constitutes a very effective and easy tool in order to improve the healthy value of milk with a potential benefit to the consumer’s health. A net or conclusive response pattern over parameters that improve the healthy value of milk to soybean and linseed oils and their blends was not clearly detected. Taken together, the results suggest some advantage for the SO75:LO25 blend considering the relative costs of both oils, the positive effects on milk, fat and protein yields, the lower hypercholesterolemic FA content of milk and the increase in VA and RA content while maintaining a healthy n - 6/n - 3 ratio and very low levels of the detrimental trans-9 C18:1 and trans-10 C18:1 FA.